Asymptomatic peripheral arterial disease, erectile dysfunction and attendant psychological impact on patients with diabetes and hypertension / Mohd Zamir Md Nor - Md Nor, Mohd Zamir (2012)
Peripheral arterial disease (PAD) and erectile dysfunction (ED) worsens the quality of life in the patients with the diseases. However, the magnitude of asymptomatic PAD and ED is not well known in Malaysia. The study was designed to determine the prevalence of asymptomatic PAD and ED in hypertensive and diabetes patients and also aims at determining the prevalence of anxiety and depression among diabetes mellitus and hypertension with ED. Ankle brachial index (ABI) was measured using doppler ultrasonic device (Nicolet Versa Lab SE, bi-directional 8 MHz) in identified diabetes and hypertension patients for PAD detection. International Index of Erectile Function (IIEF) and Hospital Anxiety Depression Scales (HADS) were used to assess ED and anxiety/depression in the study. The result of this study suggested asymptomatic PAD and ED is common among patients with diabetes and hypertension. Prevalence of asymptomatic PAD in diabetes and hypertension patients was 7.0% and 6.8% respectively. ED is prevalent in patients with diabetes (86.3%) and hypertension (77.2%). The IIEF, ABI and HADS could become routine screening among patients with diabetes and hypertension for early detection of ED, PAD and depression/anxiety to reduce the likelihood of future mortality and morbidity of the diseases.